INVESTMENT ON THE COMMUNITY INCOME AND THE ECONOMIC GROWTH IN CENTRAL JAVA - P. Eko Prasetyo Adnan (Universitas Hayam Wuruk Perbanas, 2010)
This article attempts to analyze the impact of investment on the community income and the economic growth in Central Java using the social accounting matrix (SAM) framework con- cerning people’s income and economic growth. The data were taken from Central Bureau of Statistics (BPS). Thus, it concerns production factor block, institutional block, and produc- tion sector block. It shows that investment influences the people income and economical growth. People’s income that is most affected is farming business income while that of being less affected is farming worker. The distribution of people’s income is not spread evenly among the group. Furthermore, investment production block has positive impact on the big- gest economic growth, especially on manufacturing industry sectors, except food, electricity, gasses, and drinking water. People’s income condition and economic growth which are in- fluenced by investment proved to have no difference. As such, several factors that support investment atmosphere policy: bureaucracy and licensing, infrastructure, and investment protection from illegal tolls must be given more serious attention. Beside, investment is ex- pected to grow effectively and efficiently. Next, the implication of investment policy as the main generator of economic growth trough production sector has biggest positive impact, especially on financial institution and trade sector, while investment has less impact on in- dustrial and agricultural sectors especially on food crop and food industry.